Ranking Japan’s institutions of higher education, 2017: a comparative analysis / Kenneth M. Cramer, Hyein Yoo and Dana Manning - Cramer, Kenneth M.; Hyein, Yoo; Manning, Dana (Universiti Teknologi MARA, 2019)
The present study examined the 2017 Times Higher Education annual rankings for Japanese institutions of higher learning. Based on the analytic model as mapped out previously using Canadian data, we offered a similar protocol for the top 100 institutions of higher education in Japan. Three analyses showed that: (a) overall rank correlated with individual index ranks for 9 of the 13 indices, (b) the schools appearing among the top institutions overall ranked significantly better on 8 of the 13 indices compared to schools appearing among the bottom institutions overall, and (c) schools were empirically grouped into four meaningful families or clusters whose constituent members shared a comparable profile of indices. We offer a juxtaposition of the present results to annual evaluations from Canada’s institutions of higher learning. The wider implications include an international comparison of institutions of higher learning, a proposed analysis protocol that Japanese education administrations may further pursue, and a categorical breakdown of educational institutions in Japan. Directions for future research are outlined.